Hero or Zero? Meta-Opinion in Terrorist Motivation - McCauley, Clark (Terrorism and political violence, 2025)
What is the relationship between public opinion and political action? Drawing on cases where shifts in public opinion coincided with changes in the frequency of terrorist attacks, we argue that this connection stems from the normative power of public opinion. This power is evident in the bandwagon effect, where popular opinions tend to gain even more support over time. Governments and corporations signal their belief in this power by attempting to shape public opinion with tools like bots, sockpuppets, and troll farms. Importantly, the impact of public opinion does not depend on its actual distribution, but rather on how it is perceived. People’s beliefs about what others think—meta-opinions—can differ significantly from the aggregated individual opinions typically measured in surveys. We propose new ways of measuring meta-opinions, particularly as they relate to political activism and terrorism. At the individual level, meta-opinion can provide motivation for activism or terrorism: the percentage of an ingroup that sympathizes with an ingroup grievance is the size of the audience for which an individual turning to political activism or terrorism can move from zero to hero.